Cancan! Book review - Poesio, Giannandrea (Dance Books Ltd., Alton,Hampshire (UK), 1999)
The cancan is not a dance, it is a philosophy! PALABRAS CLAVE: cancan.
Cancan! David Price, London, Cygnus Arts, 1998.